Water Dispersible Colloidal Metal and Metal Oxide Nanoparticles Synthesis for Agarwood Inoculation: A Review - Md Jahidul Islam; Md Kawsar Uddin; Mohammad Jakir Hossain (IUBAT Review, 2023)
Agarwood is one of the most expensive natural products, produced from Aquilaria Spp. These plants produce agar resin through mechanical, biological, or chemical stress. Besides these, the particles having size in the range of 1-100 nm, are known as nanoparticles, have ultra-high surface area and surface plasmon resonance, can create stress on living plants when incorporated into the plant body. Adopting this concept, we intend to produce agarwood by inoculating water-dispersible metal/metal oxide nanoparticles. Therefore, we aim to synthesize water-dispersible four noble metals (Au, Ag, Pt, Pd) and five metal oxides (Fe3O4, TiO2, SnO2, MnO2, CuO) nanoparticles in aqueous colloidal states for application in biotechnology, considering the facile synthetic routes, readily available and inexpensive precursors, and stability of the products under normal laboratory conditions for an extended period, utilizing the synthesis methods of precipitation of metal/metal oxide nanoparticles from an aqueous solution, microwave and ultrasound-assisted rapid heating methods, sol-gel methods, and surfactant-assisted microemulsion methods. We believe that by applying any of these methods, water-dispersible, long-lasting colloidal metal/metal oxide nanoparticles can be synthesized using a simple laboratory setup, without the need for sophisticated tools or instruments. IUBAT Review, 6(2): 41-76